Comparative Study of Indonesian and Malaysian Immigration Action Policies Towards Immigration Permit Abuse - Virginia, Tesalonika; Wijaya, Chandra; Barus, Lita Sari (International Journal of Social Service and Research, 2024)
The era of globalization, driven by advancements in science and information technology, has created a borderless world, transforming human relationships from national to international, and significantly impacting various aspects of human life. Globalization has promoted the movement of people between countries, including Indonesia and Malaysia, affecting the demographics, economy, culture, and social aspects of both countries. In this context, immigration regulations play a crucial role in controlling the flow of people and reflecting a country's legal sovereignty within its territorial boundaries. This study is a normative juridical research focusing on the analysis and comparison of immigration regulations and policies in Indonesia and Malaysia, using a Statutory and Comparative approach. Indonesian immigration policy, regulated in Law Number 6 of 2011 on Immigration, focuses on controlling the flow of people entering and leaving Indonesian territory to maintain state sovereignty. Meanwhile, Malaysian immigration policy, regulated in Malaysian Law Number 155 of 1959/63 on Immigration, covers crucial aspects such as entry and exit requirements, monitoring of foreigners, and law enforcement related to immigration violations. The immigration action policies of Indonesia and Malaysia towards immigration permit abuse have several similarities and differences. Although both countries have similar policies in handling immigration permit abuse, the implementation and law enforcement may differ depending on the specific context and conditions in each country.